Sustentabilidade urbana e indicadores de área verde no município de São Paulo - Maróstica, Juliana Rodrigues (2019)
Against the background of climate change, which reflects the problems faced with increasing urbanization, and, considering the reduction, and insufficient distribution of green spaces in the city, as well as its support to the urban lifestyle with regard to quality people's lives, and the environmental balance of cities. That this paper aims to analyze the indicators of green area and vegetation cover of the city of São Paulo, in order to understand how they interfere with urban sustainability. For such, it was based on the methodological and applied researches, the construction of the theoretical basis of the work took place through exploratory and bibliographical researches, since the data were collected through documentary analysis and participant observation, and finally, it was used the qualitative and quantitative method for data analysis. Finally, in response to the proposed research question: How do green area and land cover indicators interfere with urban sustainability? Considering the environmental, social and economic factors of the city, it was concluded that afforestation directly contributes to urban sustainability, since, through map analysis, the larger the tree-lined region, the better the social indicators and the better the economic valuation of their properties.